HUBUNGAN PANJANG-PANJANG, POLA PERTUMBUHAN DAN KONDISI IKAN NYALIAN, Barbodes binotatus (VALENCIENNES, 1842) DI EMPAT DANAU DI PULAU BALI - Parawangsa, I Nyoman Yoga; Tampubolon, Prawira Atmaja; Pertami, Nyoman Dati (Politeknik Kelautan dan Perikanan Sorong, 2023)
The relationship between length type, length-weight relationship and condition factors is an initial approach to fisheries management. Research related to that issue on spotted barb (Barbodes binotatus) in four lake ecosystems in Bali has never been published. This study aims to reveals information related to the relationship of length character, growth patterns and conditions of B. binotatus in four lake ecosystems in Bali. Fish sampling was carried out from August 2017 to July 2018 at Tamblingan Lake, Buyan Lake, Beratan Lake and Batur Lake which were carried out alternately. The results of this study revealed that the total length (TL), fork length (FL) and standard length (SL), each type of measurement can be used to estimate the weight of B. binotatus, but standard length was the most suitable type of measurement in estimating weights. This fish species has a positive allometric growth pattern (b>3) with an estimated condition that is in good condition.